NO gas sensing at room temperature using single titanium oxide nanodot sensors created by atomic force microscopy nanolithography - Hong, Li-Yang; Lin, Heh-Nan (Beilstein Journal of Nanotechnology, 2016)
In this work, the fabrication of single titanium oxide nanodot (ND) resistive sensors for NO gas sensing at room temperature is reported. Two atomic force microscopy nanolithography methods, nanomachining and nano-oxidation, are employed. A single titanium nanowire (NW) is created first along with contact electrodes and a single titanium oxide ND is subsequently produced in the NW. Gas sensing is realized by the photo-activation and the photo-recovery approaches. It is found that a sensor with a smaller ND has better performance than a larger one. A response of 31%, a response time of 91 s, and a recovery time of 184 s have been achieved at a concentration of 10 ppm for a ND with a size of around 80 nm. The present work demonstrates the potential application of single metal oxide NDs for gas sensing with a performance that is comparable with that of metal oxide nanowire gas sensors.
Keywords: atomic force microscopy nanolithography; photo-activation; photo-recovery; resistive NO gas sensor; titanium oxide nanodot sensor